Implementing blended-problem based learning through Google classroom in biology learning - Vitta Yaumul Hikmawati; Yeni Suryaningsih (JPBI (Jurnal Pendidikan Biologi Indonesia), 2020)
Information technology is determinant factor in creating learning environment among the 21st Century generation. This qualitative descriptive research aimed to obtain theoretical views and empirical evidences of the blended-problem based learning (PBL) application. The data were collected through non-test technique through observation. The observations were made to analyze student activities in each step of the blended-PBL. In addition, the observations were also constructed to get a view of students' off-task behaviors during learning. The results of this study indicated that Google Classroom-assisted blended-PBL was well implemented in Biology learning. The all students actively participated in searching for information related to the topics covered as well as exhibiting off-task behavior. Based on the findings in this study it can be concluded that blended-PBL can be implemented as an alternative model for learning Biology in the 21st Century.